Enforcement and the Stability and Growth Pact : How Fiscal Policy Did and Did Not Change Under Europe's Fiscal Framework - Annett, Anthony (IMF Working Papers; Working Paper ;, 2006)
The Stability and Growth Pact has been a success in numerous EU countries, especially in guiding them toward underlying fiscal balance ahead of population aging. These countries tend to be smaller, subject to greater macroeconomic volatility, and reliant on a form of fiscal governance that emphasizes targets and contracts. Most of the new members share these characteristics. For the countries less compatible with the Pact, domestic governance reforms that increase the reputational costs for noncompliance can be useful complements to the fiscal framework.